Vol. 158 : Space Engineering: VI International Forum for Young Scientists, April 26-28, 2018, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Borikov V. N. Valery Nikolaevich; Uchaykin (Uchaikin) S. V. Sergey Victorovich; Baranov P. F. Pavel Fedorovich; Ivanova V. S. Veronika Sergeevna; Dolgikh A. G. Antonina Gennadievna; Minin I. V. Igor Vladilenovich (2018, 2018)
Title screen